An Alternate Reality Game for Facility Resilience (ARGFR). (2015) - Pan, Jing; Su, Xing; Zhou, Zheng
Abstract: Disasters are immense and shocking disturbances that necessitate the collective efforts of the entire community, not just who serve as emergency management officials, to respond and recover. For better preparation, sharing of resources, engaging the public can make a substantial contribution to these improved community outcomes of disaster resilience through sharing information, identifying problems, and crafting possible solutions collectively. This research develops a framework of a serious game, which is typically used for non-entertainment educational purposes, to harness crowd wisdom and to engage them in facility resilience management. This research first examines traditional methods used in emergency response training, as well as computer simulation-based emergency drills. It next reviews the use of gaming in emergency response training, from board games to computer games utilizing simulation technologies. It is found that alternate reality games, which are driven by transmedia storytelling and intensely devoted to establishing interactions across real and fictional worlds, suit the need of emergency response training best, yet is still lacking. The alternate reality game is designed to provide appropriate challenges that are realistic, and to enhance essential aspects of the player's experience. In the framework, the reality is integrated with virtual game design, and take places offline between play sessions with knowledgeable persons checking the appropriateness of the interface. The alternate reality game is expected to engage facility occupants and to address the need of facility resilience management. Facility management team and emergency management officials are able to gather real-time information about a facility and its occupants. The idea of alternate reality game also has the potential to be applied in other aspects of facility management to achieve a shift from centralized knowledge to a collaborative model that is more adaptive to dynamic situations of a facility.